Time and Identity: The Legacy of Biafra to the Igbo in Diaspora (Nordic Journal of African Studies, 2000)
The 30th of May 1997 marked the 30th anniversary of the declaration of independence by Biafra from which the Nigerian Civil War or the Biafran War (1967-1970) ensued. In the course of this paper my interest is focussed on the legacy of Biafra and the Biafran War for the Igbo in diaspora. In the course of my research I followed discussions on the Igbo--net (an Internet discussion group whose identity exists in this double-hyphenated form) throughout 1996, and the material I am drawing on here is based on 40 discussions from 22 Igbo--netters (users of the Internet discussion group), most of whom are Igbo living in the USA. It should also be noted that all of the Igbo--netters mentioned are male. In addition, my attention will be focussed on an article published in 1996, ‘Locating Biafra. The Words We Wouldn’t Say’, which exceeds in length the combined separate writings from the Igbo--net. Further, it is the only writing under consideration produced by an Igbo female. Although my focus here is on the Igbo, among the abovementioned 22 male Igbo--netters there were also some non-Igbo as well.